Exercise, Training and Gut Function – a Physiological Perspective - Amit Bandyopadhyay (Journal of Research in Biology, 2011)
Gastrointestinal (GI) tract adapts and cope with demands of the physical activity to exert maximum output in an athlete. Various GI functions, e.g., secretion, motility, circulation, emptying pattern, absorption, colonic function, etc., undergoes various alterations not only during the event but also during the warranted demand of the training and recovery phases. It depends on the duration, intensity and frequency of the exercise mode. However, often the GI responses to exercise are individual specific. Hyperthermia induced gastric dysfunction have also been documented. Accordingly the adaptations are also evident in the gut depending on the athletic need. However, the gut barrier can prevent the extreme load on the GI tract imposed during working in the excessive stressed conditions